MENYOAL KEWENANGAN PENGADILAN NEGERI DALAM MENYELESAIKAN PERKARA WARIS MASYARAKAT MUSLIM PASCA LAHIRNYA UNDANGUNDANG NO. 3 TAHUN 2006 TENTANG PERADILAN AGAMA (Studi Kasus di Kabupaten Jombang Jawa Timur) - Ilham Tohari (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
The title of this article is: Questioning the Authority of theDistrict Court in Resolving Inheritance Cases of MuslimCommunity after The Enactment of Law No. 3 Year 2006 on theReligious Court (A Case Study in Jombang District Court, EastJava). The focus of this article includes (1) The reasons JombangMuslim community chose the District Court in resolving theirinheritance case; (2) The reasons the District Court receive,examine and make decisions on inheritance case of Muslim Society.These points are analyzed descriptively, qualitatively, andphenomenologically, using the approach of law sociology and lawpolitics.